INTEROGATIF DALAM NOVEL “HATIKU BUKAN PUALAM” KARYA SAUT POLTAK TAMBUNAN (Interrogative in Novel “Hatiku Bukan Pualam” By Saut Poltak Tambunan - Rahmatiah Rahmatiah (SAWERIGADING, 2009)
This writing aims to identify interrogative sentence in a novel written by Paut Soltak Tambunan and analyze interrogative sentence in that novel. Novel which is analyze in this writing is “Hatiku Bukan Pualam”. This writing uses descriptive method. Identification done find various kind of interrogative  sentences.